Quality control for offsite construction: long distance transportation impact / Raja Anis Syafinas binti Raja Muhammad and Noor Sahidah binti Samsudin - Raja Muhammad, Raja Anis Syafinas; Samsudin, Noor Sahidah (2019)
This paper focused on precast component defects that may occur to the long-distance transportation to the site construction field. Nowadays, the Industrialized Building System (IBS) in Malaysia is rapid growth in the number in a perfect tune. Besides, the Government of Malaysia itself puts great effort through this system in construction industry. Nevertheless, most of the stakeholders still have negative perceptions in IBS and are unable to foresee the benefits of this approach. Feedback from the past experiences associated using IBS component panels tense to approach such a joint failure, water leaking, poor qualities and cost overrun. To maintain the quality of the IBS products this action must be conceded. Hence, the information that be collect is to identify the problems factors regarding the issues of the defects on precast components especially on the shipping transportation of panels to the site and also to determine the current used supporter system for the element of precast arrangement on the truck. In addition, solution on reducing the impact causes on the precast components is through the innovation idea on padding or impact and vibration absorber or cushion system is needed. Simultaneously, enhancing and giving a better perception towards IBS will create a better understanding and demand for IBS adoption in construction industry.